2020
DOI: 10.1186/s12887-020-1969-6
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of kindergarten children meeting the WHO guidelines on physical activity, sedentary behaviour and sleep and associations with adiposity in urban Beijing

Abstract: Background: World Health Organisation (WHO) Guidelines on Physical Activity, Sedentary Behaviour and Sleep for Children under 5 Years of Age were released in 2019. The aim of this study was to examine the proportion of Chinese kindergarten children who met each individual guideline and each combination of the guidelines and the associations with adiposity. Methods: Participants were 254 kindergarten children aged 4.1-6.3 years recruited from three kindergartens in urban area of Beijing. Physical activity, sede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
88
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 39 publications
13
88
6
1
Order By: Relevance
“…Pediatric obesity is often cited as a major and pressing health concern [1,2] that can lead to numerous physiological (e.g., high blood pressure, type 2 diabetes) and psychological (e.g., depression, poor quality of life, low self-esteem) issues throughout the lifespan [3][4][5]. Consistent with international trends [1], national data has demonstrated that China has experienced an alarming increase in pediatric obesity in the past 20 years, as well as associated physiological conditions (i.e., hypertension, diabetes) [6,7]. According to Wang and colleagues [6], this steady increase in obesity in China has coincided with the country's rapid economic growth, and may be a result of multiple lifestyle factors, including unhealthy diet, lack of physical activity (PA), and increased sedentary behavior.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Pediatric obesity is often cited as a major and pressing health concern [1,2] that can lead to numerous physiological (e.g., high blood pressure, type 2 diabetes) and psychological (e.g., depression, poor quality of life, low self-esteem) issues throughout the lifespan [3][4][5]. Consistent with international trends [1], national data has demonstrated that China has experienced an alarming increase in pediatric obesity in the past 20 years, as well as associated physiological conditions (i.e., hypertension, diabetes) [6,7]. According to Wang and colleagues [6], this steady increase in obesity in China has coincided with the country's rapid economic growth, and may be a result of multiple lifestyle factors, including unhealthy diet, lack of physical activity (PA), and increased sedentary behavior.…”
Section: Introductionmentioning
confidence: 91%
“…Given issues concerning pediatric obesity in China [6,7], research examining adherence to the 24-h movement guidelines may be timely. However, few studies have examined adherence to 24-h movement guidelines in China [7,13,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations